(untitled) (Advances in Applied Mathematics and Mechanics, 2021)
In this paper, an efficient class of finite difference nested multi-resolution weighted essentially non-oscillatory (WENO) schemes with increasingly higher order of accuracy is presented for solving hyperbolic conservation laws on structured meshes. The crucial idea is originated from [44,46]. We only use the information defined on a series of nested unequal-sized central spatial stencils in high-order spatial approximations. These new nested multi-resolution WENO schemes use the same large central stencil as the same order classical WENO schemes [3,21] without increasing the number of the total spatial stencils, could obtain the optimal order of accuracy in smooth regions, and could control spurious oscillations nearby strong shocks or contact discontinuities by gradually degrading from ninth-order to seventh-order, fifth-order, third-order or ultimately to the first-order accuracy. Associated linear weights can be set as any positive numbers on condition that their summation is one. Therefore, these new WENO schemes are simple to construct and can be easily implemented to arbitrarily high-order accuracy in multi-dimensions. Some benchmark examples are illustrated to show the good performance of these new nested multi-resolution WENO schemes, especially in terms of robustness and low numerical dissipation.